Structural rewiring of IL-7R dimerization by an oncogenic transmembrane mutation can be reversed by rational design - Qian Wang; Min Chen; Asma Lasram; Saana Vihuri; Angela Z. Chou; Weixin Bian; Zhiming Dai; Outi Haapanen; Giray Enkavi; Christoph Pollmann; Ilpo Vattulainen; Tiantian Cai; et al. (Proceedings of the National Academy of Sciences, 2026)
Mutations within the transmembrane domains (TMDs) of single-pass transmembrane receptors often cause aberrant, ligand-independent receptor signaling associated with diverse malignancies, but their mechanism of action remains largely unknown. These TMD mutations are generally not targetable as they are buried in the membrane. Here, we determined the mechanism of a gain-of-function (GOF) TMD mutation of interleukin-7 receptor (IL-7R) associated with T cell acute lymphoblastic leukemia and addressed the possibility of directly targeting the TMD mutation by using rationally designed transmembrane helices to restore order to uncontrolled signaling. We find that the GOF mutation of IL-7R severely shifts the TMD homodimerization interface, causing the receptor to homodimerize in a geometry that activates downstream signaling independent of ligand. Designed transmembrane helices that interfere with the new interface, delivered with mRNA technology, selectively block ligand-independent but not ligand-dependent signaling. Our study provides a conceptual framework for understanding and repairing disease-causing TMD mutations of single-pass cytokine receptors.